A 5‐year longitudinal association between dietary fermented soya bean (natto) intake and tooth loss through bone mineral density in postmenopausal women: The Yokogoshi cohort study. (4th January 2021) - Iwasaki, Masanori; Sato, Misuzu; Yoshihara, Akihiro; Saito, Toshiko; Kitamura, Kaori; Ansai, Toshihiro; Nakamura, Kazutoshi
Abstract: Objective: In this 5‐year cohort study, we aimed to determine whether the intake of natto, a fermented soya bean food product, has an indirect effect on tooth loss incidence through BMD changes among postmenopausal women. Background: Evidence indicates (1) that natto has a beneficial effect on bone health and (2) that a decrease in bone mineral density (BMD) is associated with tooth loss. Methods: The study recruited 435 postmenopausal women (average age = 64.2 years). Natto intake (exposure) was assessed at baseline using a food frequency questionnaire. Lumbar spine BMD and number of teeth were measured at baseline and 5‐year follow‐up. BMD change (mediator) and the number of teeth lost (outcome) over time were calculated. The mediation model consisted of these 3 variables. Mediation analysis was performed to test the indirect effect of the natto intake measured through BMD change on tooth loss. Results: During the study, the mean number of teeth lost was 1.2 (standard deviation = 1.8), and the mean BMD decline was 2.5% (standard deviation = 7.1). After adjusting for potential confounders, increasing habitual natto intake was significantly indirectly associated with a lower incidence of tooth loss mediated by BMD change (incidence rate ratio of tooth loss among women with "≥1 pack/day" natto intake was 0.90 [95% confidence interval = 0.82‐0.99] compared to those with natto consumption of "rarely"). Conclusions: Dietary natto intake is significantly indirectly associated with a lower incidence of tooth loss among postmenopausal women, and systemic bone density could be a mediator of this association.